2020
DOI: 10.1177/1559325820969597
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic Acid Synergizes With Low-Level Ionizing Radiation to Modulate Bisphenol Induced-Lung Toxicity in Rats by Inhibiting JNK/ERK/c-Fos Pathway

Abstract: Bisphenol A (BPA) is a low molecular weight chemical compound that has a deleterious effect on the endocrine system. It was used in plastics manufacturing with injurious effects on different body systems. Occupational exposure to low-level ionizing radiation (<1 Gy) is shown to attenuate an established inflammatory process and therefore enhance cell protection. Therefore, the objective of this study was to investigate the protective effect of boswellic acid (BA) accompanied by whole-body low-dose gamma radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Lung cells include estrogen receptors, which stimulate their growth. 23 According to the previous studies, 7 , 10 which found that BPA-induced lung injury in rats, the present study revealed that exposure to BPA along with ionizing radiation interactions influences cellular responses and induces small cell lung cancer (SCLC) in female rats confirmed by bio and histology analysis. The estrogen receptor GPER mediated this effect through which the BPA/IR prompted activation signals GPCR/EGFR/KRAS/ERK1/2 stimulates upregulation of MMP-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Lung cells include estrogen receptors, which stimulate their growth. 23 According to the previous studies, 7 , 10 which found that BPA-induced lung injury in rats, the present study revealed that exposure to BPA along with ionizing radiation interactions influences cellular responses and induces small cell lung cancer (SCLC) in female rats confirmed by bio and histology analysis. The estrogen receptor GPER mediated this effect through which the BPA/IR prompted activation signals GPCR/EGFR/KRAS/ERK1/2 stimulates upregulation of MMP-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 68%
“…BPA also stimulates MAPK/ERK and p-JNK signaling pathway members' transcription and translocation. 7 Moreover, living organisms are exposed to ionizing radiation (IR) in everyday life, which is a phenomenon that has the potential to cause harmful human health impacts. Staff in the sectors of radiation and nuclear-powered engineering, patients having diagnostic procedures and/or treatment activities, and medical workers accidentally exposed to some degree of radiation are among the people and humanities who are exposed to IR from natural and manufactured sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific research clarified the distribution of NOX homologs in the colon and confirmed their contribution to the pathological processes of intestinal diseases . It is reported that the transcript levels of the NOX gene in rat lungs are overexpressed due to BPA exposure . Xia et al reported that BPA promotes ROS formation in human colon cancer cells in a NOX-dependent manner .…”
Section: Discussionmentioning
confidence: 99%
“…It decreases the oxidative damage of the bio-molecules (NADPH and MDA) and inflammatory variables (IL-6, TNF-α, and MPO). It also inhibits lung inflammation by preventing JNK/ERK/cFos pathway 28 .…”
Section: Anti-microbial Activitymentioning
confidence: 99%